2005
DOI: 10.1063/1.1921336
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of porous alumina from vacuum ultraviolet to midinfrared

Abstract: Porous alumina was fabricated and optically characterized over a wide spectral range. Layers were formed electrochemically in oxalic acid solution from 10-m-thick aluminum films evaporated onto silicon wafers. The layer formation was monitored with in situ spectroscopic ellipsometry in the visible and near-infrared wavelength range to accurately determine the thickness and dielectric functions. Anisotropy due to the columnar nature of the porous structure was determined using optical modeling. The porous alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Application of spectroscopic ellipsometry to the study of optical properties of nanoporous alumina structures obtained by electrochemical aluminum anodization has already been performed by different authors [24,25], and differences depending on the pore radii/porosity of the studied samples have been reported [26]. Ellipsometry measures a change in the polarization as light reflects or transmits from a material structure, and the ellipsometric angles Ψ and ∆, determine the differential changes in amplitude and phase, respectively (tan(Ψ) e i∆ = r p /r s , where r p y r s are the amount of light reflected in the perpendicular and parallel planes of incidence [27]).…”
Section: Spectroscopic Ellipsometry Analysismentioning
confidence: 99%
“…Application of spectroscopic ellipsometry to the study of optical properties of nanoporous alumina structures obtained by electrochemical aluminum anodization has already been performed by different authors [24,25], and differences depending on the pore radii/porosity of the studied samples have been reported [26]. Ellipsometry measures a change in the polarization as light reflects or transmits from a material structure, and the ellipsometric angles Ψ and ∆, determine the differential changes in amplitude and phase, respectively (tan(Ψ) e i∆ = r p /r s , where r p y r s are the amount of light reflected in the perpendicular and parallel planes of incidence [27]).…”
Section: Spectroscopic Ellipsometry Analysismentioning
confidence: 99%
“…For obtaining ε , Goad and Moskovits [8] used the Maxwell-Garnett approximation, which is strictly valid for very small metal inclusions in the dielectric [12]. Given the nature of the present samples (parallel cylindrical metallic NW in a dielectric matrix), Bruggeman's effective medium approximation [12] is used instead; which already has been used for the unfilled PAM [11,17]. It is more appropriate for the rather high metal filling fraction f m of these samples.…”
mentioning
confidence: 98%
“…The relation between the optical and structural properties of PAA has been studied by spectroscopic ellipsometry [9]. Similar ellipsometric studies have recently identified resonant transitions in the IR and UV regions [10]. It has been also shown that PAA PL depends on the preparation conditions, like annealing [6] or substrate [11,12].…”
mentioning
confidence: 99%